Memories of a Malabar Lady : M. Sreekumari Vasudevan's Reminiscences of Life with Justice K.S. Menon 1926-1956 - Vasudevan, M. Sreekumari (Brill | Manohar Publishers & Distributors, 2022)
Memories of a Malabar Lady: M. Sreekumari Vasudevan's Reminiscences of Life with Justice K.S. Menon, 1926-1956 , emerged from conversations between a mother and son spanning a decade. It recalls Sreekumari Vasudevan's early life in the company of her father, K.S. Menon, whose career in the law took them from Mamballikalam, the matrilineal family estate in Malabar, to Madras, other places in Madras Presidency, and the princely state of Jodhpur. It is a story of smaller units and individuals in a sprawling joint family and a young woman's widening arc of experience. The book is remarkable for how Hari Vasudevan combines the skills of a professional historian and the empathy of a son to fashion the story of an era through the personal, modest and smaller scenes of historical change. This book was in manuscript form when Hari passed away, and was finalized for publication by Ravi Vasudevan.